African American management history : insights on gaining a cooperative advantage - Prieto, Leon C.; Phipps, Simone T. A. (Emerald Publishing Limited, 2019)
The most successful business leaders always have their own compelling philosophies, but all too often the thoughts and ideologies of high-profile African American leaders are forgotten or passed over. The ideas and practices of these visionary leaders, sometimes heralded within their own communities, are often ignored by mainstream media and, over time, many of their contributions are forgotten. Leadership experts Leon C. Prieto and Simone T.A. Phipps re-light these extinguished torches reflecting on some of the leading black business pioneers of the late 19th and early 20th century. Exploring views that embrace the traditional African philosophies of cooperation, this study of such influential figures brings to light how heavily the "golden age of black business" was impacted by the "cooperative advantage" possessed by leaders such as Charles Clinton Spaulding, John Merrick, Alonzo Herndon, Annie Turnbo-Malone, Madam C.J Walker, and Maggie Walker. Ultimately, what Prieto and Phipps bring to light is the common thread that pulls these leaders together--namely, the love they had for their communities--and what they show is that contemporary entrepreneurs of African descent would do well to regain a cooperative advantage in order to achieve the levels of success that existed in the past. For its recovery of important strands within African American history, and for the practical advice it gleans from those strands, this refreshing study is a must-read for business students, managers, entrepreneurs and leaders of all backgrounds. The history here brought to light demonstrates to students that they too can succeed at managing any enterprise, no matter the challenges they may face.
Includes index.
Keywords: Management.; African Americans -- History.; Business & Economics -- Management.; Management: leadership & motivation.; elektronické knihy; electronic books